Growth, maturity status, motor proficiency and fitness of participants and non-participants in organised sports 7–10 years - Robert M. Malina; António Antunes; Élvio Gouveia; Gonçalo Marques; Martine Thomis; Duarte Freitas (Annals of Human Biology)
Background Lifestyles of contemporary children are largely organised with relatively little time for free play.Aim To compare the growth, maturity status, motor proficiency and physical fitness of non-participants and participants in organised sports 7–10 years.Subjects and methods Height, weight, skeletal age (SA), physical activity, fundamental motor skills, motor coordination and fitness were assessed in 234 boys and 235 girls. Sex-specific comparisons of the characteristics of sport participants and non-participants 7–8 and 9–10 years were evaluated with Student’s t and Mann–Whitney U tests.Results Boys and girls in each age group active in sport had significantly higher levels of sport-related physical activity. At 7–8 years, boys active in sport were significantly taller and heavier than peers not active in sport, while girls not active in sport performed significantly better in ball rolling and balance. At 9–10 years, boys active in sport were more proficient in catching, while girls active in sport were more proficient in hopping and side-to-side jumping.Conclusion SA and performances among children 7–10 years active and not active in sport were largely non-significant statistically, while those active in sport were physically more active.